(untitled) (World Bulletin of Management and Law, 2022)
It is known that the legal democratic state and free civil society develop in a country where the rule of law is provided, and the foundations of the institutions of civil society are formed. According to the laws of the Republic of Uzbekistan, non-governmental organizations: among political parties, women’s organizations, youth organizations, the Mahalla (mahallah) institute and religious organizations are also civil society institutions. The development of society, on the one hand, depends on the activities of civil society institutions; on the other hand, constructive cooperation between them. The study of the organizational legal framework of the interaction of religious organizations with the mahallah institute and further improvement of cooperation between them provides an opportunity to make practical proposals on studying and eliminating existing problems related to their prospects.